Preparing the populations: identifying educational needs and communication networks regarding zoonotic-disease outbreaks - Bausch, Mariah E. (Kansas State University, 2019)
As zoonotic-disease epidemics sweep through the country, research is needed to determine preventative measures and control methods to minimize the impact. Previous research has indicated education and communication play major roles in controlling zoonotic-disease outbreaks. This study looked at the educational experiences, communication plans, and levels of preparedness of key audience groups of: livestock producers, veterinarians, medical professionals, and emergency managers. The following questions guided this study: What are audiences’ educational experiences related to zoonotic-diseases? What are audiences’ experiences with communication planning for zoonotic-disease response? What are audiences’ social networks and related information sources for zoonotic-disease? A qualitative approach was taken through semi-structured interviews to determine the communication channels and educational needs of 40 participants throughout targeted counties in Kansas. Counties were selected based on animal population and urban areas throughout the state. Purposive sampling was initially used to contact participants and snowball sampling was used to expand the population. Data was analyzed using Glaser’s constant comparative. Social Network Theory guided the study in evaluating the relationships between audience groups. Diffusion of Innovations was also used to identify social networks as well as influences on educational practices. Major themes emerged when responses were identified within all four of the audience groups. All audience groups had innovator and majority adoption categories. Past education often occurred through organizational trainings which developed into a major theme. Two major themes associated with future educational learning preferences were online modules and workshop-based presentations. A need for more collaboration among audience groups and other entities was also identified as a major theme. Veterinarians were seen as having a major role in communication needs and dissemination efforts among all audience groups. Kansas State University was also seen as a major theme in providing information to audience groups. Recommendations were suggested for research, communication practices, and education. Future studies in understanding a larger population of audience groups, public perception of zoonotic-diseases, and the impact of social media on disseminating information about disease outbreaks should occur. Training and educating audience groups about the importance of crisis communication and the benefits of being transparent are essential for communication practices. Improving education about zoonotic-disease will increase the likelihood of adopting prevention measures and increase collaboration among audiences. Overall, improving planning, prevention, and collaboration through education and communication is critical to controlling and preventing zoonotic-disease outbreaks.
Keywords: Zoonotic-disease; Social Network Analysis; Crisis communication; Diffusion of Innovation; Education